Purple bacteria reaction centers in photovoltaic applications - Białek, Rafał (My University, 2021)
Nature had billions of years to optimize the processes occurring in living organisms, which makes it a perfect example to follow and source of inspiration for humanity for centuries. One of this examples is photosynthesis, whose first steps are nothing else but the conversion of light energy to the flow of electrons (electrical current). One of the strategies to utilize Nature’s optimization achievement is to isolate photosynthetic proteins and use them as photoactive material in biohybrid photovoltaic devices. In this thesis, the focus is put on the understanding of the operation of Rhodobacter sphaeroides reaction centers (RCs) with possible applications in biohybrid photoelectrochemical devices. First biohybrid system presented in this work is based on TiO2 mesoporous layer as a substrate for RCs immobilization. It resulted in relatively low photocurrents, but generated in both cathodic and anodic ways. Second studied system is a redox-active hydrogel (built with Os-complex based polymers) with embedded RCs. This was characterized by generation of photocurrent with significant internal quantum efficiency (). To summarize, work presented in this thesis contributed to understanding of the operation of biohybrid devices, which along with work of other researchers in the field, might create a fully understood picture of it in the future.

Natura przez miliardy lat optymalizuje procesy zachodzące w żywych organizmach, co czyni ją idealnym wzorem do naśladowania. Jednym z przykładów jest fotosynteza, której pierwsze etapy są niczym innym jak przekształcaniem energii słonecznej na przepływ elektronów. Jedną ze strategii wykorzystania osiągnieć optymalizacyjnych natury jest użycie izolowanych białek fotosyntetycznych jako materiału pochłaniającego światło w biohybrydowych urządzeniach fotowoltaicznych. W tej rozprawie doktorskiej nacisk kładziony jest na zrozumienie działania centrów reakcji Rhodobacter sphaeroides z możliwym zastosowaniem w biohybrydowych urządzeniach fotoelektrochemicznych. Pierwszą opisaną w pracy elektrodą biohybrydową jest układ oparty na mezoporowatej warstwie TiO2 użytej jako baza do przyłączenia centrów reakcji. Wartości fotoprądów dla opisanej konstrukcji okazały się względnie niskie, lecz ich przepływ możliwy był w obu kierunkach. Drugim zaprezentowanym układem jest hydrożel o właściwościach redoks z unieruchomionymi w nim centrami reakcji. Zaobserwowano wysoką wydajność kwantową () generacji fotoprądu w tych układach. Podsumowując, praca zaprezentowana w tej rozprawie przyczyniła się do lepszego zrozumienia działania układów biohybrydowych, co razem z wynikami innych grup badawczych może w przyszłości ukazać kompletny, w pełni zrozumiały obraz działania tych urządzeń.
Centra reakcji bakterii purpurowych w zastosowaniach fotowoltaicznych
Wydział Fizyki
Keywords: purple bacteria; photovoltaics; biohybrid systems; electrochemistry; spectroscopy; bakterie purpurowe; fotowoltaika; układy biohybrydowe; elektrochemia; spektroskopia